Special judo fitness test classificatory table for female judo athletes - Sterkowicz-Przybycien, K. (4th European Science of Judo Symposium. Budapest, April 25th 2013, 2013)
Conflicting results were documented in Special Judo Fitness Test (SJFT) for mean parameters of performance and gender of judo athletes matched by age and sports level. Therefore, it is disputable whether SJFT classificatory table, prepared for males, should be also used for females. The goal of the study was to prepare the original standards to allow coaches and researchers to control and evaluate training effects in female judokas. Material and Methods. The scientific studies were used to collect the research material containing information on female judo athletes who were tested in SJFT. The results were derived from international databases which are available in the Internet. Statistical analysis included the results obtained from 11 relevant studies published between 1997 and 2012. Combined means and standard deviations were computed based on reports concerning 198 individual results in SJFT. A five-degree scale was adopted as follows: Excellent = highest 5%, Good = next highest 15%, Regular = middle 60%, Poor = next lowest 15%, Very poor = lowest 5% . Results. The study presents the Special Judo Fitness Test Classification Table for female judokas. The normative data included Heart Rate registered immediately after the test, Heart Rate obtained 1 minute after test, Number of Throws completed during the test and Index in SJFT. As an example, the effect of the phases in the menstrual cycle on SJFT results was evaluated using the mean results obtained for female athletes. The evaluation was conducted according to the normative data. Conclusion. Interactions between the results of testing judo-specific fitness and menstrual patterns response in athletes can be considered during their evaluation using a new classificatory table. With this careful diagnosis, training loads and fighting tactics during competition should be individually modeled.